Entrepreneurs’ negative feelings and the covid-19: an analysis of tweets - Pagotto, Daniel; Barbosa, Rodrigo; Borges, Cândido; Nassif, Vânia (Journal of Sustainable Competitive Intelligence, 2022)
Purpose: The objective of the present research was to analyze the interference of the COVID-19 pandemic in the negative feelings of entrepreneurs. Methodology/approach: To achieve the proposed objective, we analyzed posts made by entrepreneurs on the social network Twitter in the first half of 2020, the beginning of the pandemic. A sentiment analysis was performed on the obtained tweets, with a focus on the negative feelings of disgust, sadness, fear, and anger. Originality/Relevance: Previous studies have shown that pandemics can generate negative impacts on people's psychological and emotional health. In this context, entrepreneurs' business survival can be jeopardized, as poor mental health can result in decreased planning, problem-solving, and decision-making abilities. Key findings: Feelings of sadness and fear showed the highest percentage increase among the entrepreneurs analyzed in the period. These feelings can lead to physical and emotional illnesses. Future research can apply algorithms that can broaden the classification of feelings, including adding positive valence feelings to the analysis. Theoretical/methodological contributions: The present work contributes by introducing a technique that has been pointed out as promising in management and entrepreneurship studies in the challenging context of the pandemic caused by the coronavirus.